2013
DOI: 10.1245/s10434-013-3215-z
|View full text |Cite
|
Sign up to set email alerts
|

STMN-1 Gene: A Predictor of Survival in Stage IIA Esophageal Squamous Cell Carcinoma After Ivor-Lewis Esophagectomy?

Abstract: Even localized ESCC are potential to relapse with poor prognosis. This study demonstrates that STMN-1 level is an independent prognostic factor after Ivor-Lewis esophagectomy. In addition, assessment of STMN-1 level could improve stratification of stage IIA ESCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…We have previously reported that STMN1 is frequently overexpressed in esophageal squamous cell carcinoma tissue and significantly upregulated in esophageal cancer cell lines [12]. Our clinical data suggested that STMN1 is a predictor of survival in esophageal cancer, and laboratory data confirmed that upregulated STMN1 level in cell lines was oncogenic.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We have previously reported that STMN1 is frequently overexpressed in esophageal squamous cell carcinoma tissue and significantly upregulated in esophageal cancer cell lines [12]. Our clinical data suggested that STMN1 is a predictor of survival in esophageal cancer, and laboratory data confirmed that upregulated STMN1 level in cell lines was oncogenic.…”
Section: Discussionsupporting
confidence: 66%
“…STMN1 was originally identified as a phosphoprotein upregulated in leukemia [11]. Since then, it has also been reported to be overexpressed in solid tumors, including in our previous research, and we found that STMN1 was highly overexpressed in esophageal squamous cell carcinoma and was related with malignancy of the disease and poor clinical outcome [12]. In our recent research, we also reported that STMN1 is associated with lymphatic metastatic recurrence in pN0 ESCC [13].…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Overexpression of STMN1 in human cancer not only disrupts normal cell-cycle progression but, more importantly, facilitates polyploidy/aneuploidy of the targeted cells [15]. Stathmin 1 has been implicated in both G1-S and G2-M checkpoint control of cell-cycle progression by influencing the dynamics of microtubule formation and progression of the cell cycle [30]. Kang et al [42] found that aberrant p53 immunoreactivity was associated with higher STMN1 expression in gastric adenocarcinoma, suggesting that overexpression of STMN1 might be partially due to inactivation of tumor-suppressor gene p53.…”
Section: Discussionmentioning
confidence: 99%
“…STMN1 promotes microtubule depolymerisation by sequestering tubulin (Marklund et al , 1996; Rubin and Atweh, 2004; Budhachandra et al , 2008) and stimulating catastrophes (Howell et al , 1999). High STMN1 expression is associated with poor prognosis in a variety of human cancers such as nasopharyngeal carcinoma (Cheng et al , 2008; Hsu et al , 2014), distal oesophageal adenocarcinoma (Akhtar et al , 2014a), oesophageal squamous cell carcinoma (Akhtar et al , 2014b), breast cancer (Golouh et al , 2008), hepatocellular carcinoma (Hsieh et al , 2010), cholangiocarcinoma (Watanabe et al , 2014), prostate cancer (Mistry and Atweh, 2006), colorectal cancer (Wu et al , 2014), and non-small cell lung cancer (NSCLC; Nie et al , 2015). STMN1 was suggested as a possible prognostic marker and a potential therapeutic target for GC (Jeon et al , 2010; Kang et al , 2012; Ke et al , 2013).…”
mentioning
confidence: 99%